The Importance of Knowledge Management in Increasing the Innovation of Tourism Staff: A Case Study at Taman Mini Indonesia Indah (TMII) - Sukoco, Iwan; Irvawan, Robby; Hermanto, Bambang; Abdul Muhyi, Herwan (Technium Social Sciences Journal, 2021)
The knowledge inherent in employees is an important thing to be managed by all business sectors including tourist attractions such as Taman Mini Indonesia Indah (TMII), because with good knowledge, companies or institutions will be able to develop various innovations. But the problem is what if the existing knowledge among employees is not evenly distributed, there are some people who are experienced or have a lot of knowledge, but there are also some people who still do not understand the knowledge they should have. This research is aimed at answering the question whether knowledge management has been understood by the staff working at Taman Mini Indonesia Indah (TMII), what are the obstacles encountered in implementing knowledge management, and what efforts should be made so that the staff can have the ability to manage their knowledge. This is a qualitative research with a case study approach. Data collection was carried out by interviewing 15 staff. The results showed that knowledge management, when accompanied by knowledge sharing, will produce great innovation for the company and the company must initiate knowledge sharing among employees so that each employee can inspire other employees to create innovation.